Integrating Islamic Values into Natural Science Education to Foster Environmental Awareness: A Systematic Literature Review - Anip Dwi Saputro; Devid Dwi Erwahyudin; Sigit Dwi Laksana; Adib Khusnul Rois (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Natural science education plays a critical role in shaping students’ understanding of the natural world and their responsibility toward environmental sustainability. Within faith-informed educational contexts, science learning is increasingly viewed not only as an empirical endeavor but also as a medium for ethical and spiritual reflection. This study aims to synthesise existing research on the integration of Islamic values into natural science education in fostering environmental awareness among elementary school students through a Systematic Literature Review guided by the PRISMA 2020 framework. Relevant studies published between 2018 and 2024 were systematically identified, screened, and analysed using a thematic synthesis approach. The findings indicate that the integration of Islamic ethical principles, including stewardship, responsibility, balance, and care for cleanliness, is consistently associated with enhanced environmental awareness at cognitive, affective, and spiritual levels. Integrated thematic learning, contextual instruction grounded in Qur’anic reflection, and experiential activities are widely reported as supportive pedagogical strategies. This review contributes a consolidated conceptual reference for values-informed science education and highlights directions for future empirical research on sustainable environmental learning in primary education contexts.